NEW YORK TIMES ON THE OCTOBER REVOLUTION OF 1917 - Tatyana Pantyukhina (Гуманитарные и юридические исследования)
The article analyses the coverage of the Revolution of 1917 in Russia by the American newspaper New York Times. It was the most influential print media which expressed opinions of the political establishment. In November, 1917, New York Times featured the Russian Revolution as the main international news. The publications contained mere facts without conclusions but the comments sounded pessimistic. An object of deep concern was the impact of the Revolution on the role of Russia in WWI. The reports from Russia written in a dry telegraphic style could just confuse an American reader. In order to provide an insight into the Revolution the newspaper published analytical materials such as the essay "Bolsheviki's Chief" by the Russian revolutionary immigrant M. Olgin. Apart from analytical materials New York Times published some narratives by witnesses. One of them described the procedures of the revolutionary court in Petrograd through the trial of countess Panin. Another narrative written by an American businessman S.Lovich provided vivid sketches of everyday life in revolutionary Petrograd. To conclude, New York Times not only covered the twists and turns of political life but also the specific character of revolutionary daily routine.